Model Pendidikan Politik Himpunan Mahasiswa Islam Cabang Padang - Fadli Ilham; Hasrul Hasrul; Susi Fitria Dewi (Universitas Negeri Medan, 2020)
This article aims to describe how the model of integrated political education based on the five qualities of the Padang branch of the Islamic Student Association (HMI). The problem is focused on the Padang branch HMI integrated political education model. This research uses a qualitative approach. Data is collected through documentation studies, interviews, observations, and FGD (focus group discussion). Data were analyzed using data analysis techniques consisting of data reduction, data presentation and decision making. Data validity was tested by source triangulation. This study concludes that the integrated political education model based on the five qualities of the HMI aspirants of the Padang branch is based on the objectives of the HMI with formal, non-formal and informal forms of political education.